Broadcasting the branded burgis the Philippine middle class in Nestle's Kasambuhay, Habambuhay centennial celebration campaign - Rivera, Jan kevin Moises 1991-; Guieb, Eulalio R. III. (2012)
"This study aims to answer how socio-economic classes are represented in broadcast mass media advertisements. The research problem is uncovering the mediated narrative myth of the Philippine middle class as shown in the centennial celebration campaign of Nestle Philippines, entitled Kasambuhay, Habambuhay (Companion in Life, For Life). The campaign consists of ten anthologized short films. The main premise of the thesis is that the consistent advertising and marketing message of Nestle i.e, showing that consuming "Good Food" gives value to "Good Life", a specific socio-economic lifestyle and way of life. Hence, the thesis deconstructs these broadcast materials to show that the "Good Life" points to the attributes of the Philippine middle class as given value by "Good Food". The research is guided by two frameworks: Igor Kopytoff's economic anthropological insight on the cultural biography of things and Roland Barthes's semiological approach to interpreting stories-the theoretical and methodological framework of narrative mythography. The analysis consists of two levels. The first order of analysis is establishing the momentous and continuing biography of Nestle products as informed by local culture and context. The second older is uncovering attributes of the middle class as shaped by Nestle products."
Vita.
Undergraduate thesis (A.B. Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Kasambahay, Habambuhay; Nestle Philippines; Branding (Marketing) -- Philippines